2020
DOI: 10.1038/s41598-020-73330-7
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone increases blood glucose via hepatic progesterone receptor membrane component 1 under limited or impaired action of insulin

Abstract: Hepatic gluconeogenesis is the main pathway for blood glucose maintenance activated during fasting. Retardation of insulin action, such as in diabetes mellitus, activates gluconeogenesis during the fed state. While the role of progesterone (P4) in diabetes is controversial, the P4 receptor, progesterone receptor membrane component 1 (PGRMC1), is known to stimulate pancreatic insulin secretion. We investigated the role of P4, via hepatic PGRMC1, during gluconeogenesis. The PGRMC1 binding chemical, AG-205, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 30 publications
1
42
0
5
Order By: Relevance
“…These phenotypic discrepancies in Pgrmc1 KO mutants may be due to the differences in model organisms, gene knockout strategy, and organ-specific roles of PGRMC1; nevertheless, it is obvious that PGRMC1 plays a critical role in female reproduction. Beside its classical function such as steroid hormone synthesis [ 26 , 27 ] and metabolic function as a non-genomic progesterone receptor [ 28 , 29 , 30 , 31 ], the relevance between Pgrmc1 and cancers has been suggested in diverse organs. One example is the role of Pgrmc1 in breast cancer [ 32 , 33 ], as Pgrmc1 has been recently identified to play important roles in the survival duration and metastasis of breast cancers in a murine PyMT model [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypic discrepancies in Pgrmc1 KO mutants may be due to the differences in model organisms, gene knockout strategy, and organ-specific roles of PGRMC1; nevertheless, it is obvious that PGRMC1 plays a critical role in female reproduction. Beside its classical function such as steroid hormone synthesis [ 26 , 27 ] and metabolic function as a non-genomic progesterone receptor [ 28 , 29 , 30 , 31 ], the relevance between Pgrmc1 and cancers has been suggested in diverse organs. One example is the role of Pgrmc1 in breast cancer [ 32 , 33 ], as Pgrmc1 has been recently identified to play important roles in the survival duration and metastasis of breast cancers in a murine PyMT model [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish knockouts produce analogous results [ 20 ]. A separate N-terminal frameshift mutation knockout of mouse PGRMC1 has revealed roles in modulation of hepatic fatty acid synthesis [ 21 ], mammary gland development [ 22 ], and regulation of hepatic glycolysis/gluconeogenesis [ 23 ]. The PGRMC1 crystal structure has provided substantial insight into PGRMC1 biology, its probable role as a sensor of gases, such as CO and NO, and the relationship of these to the redox state of heme iron [ 24 , 25 ].…”
Section: Recent Advances and Current Statusmentioning
confidence: 99%
“…Previous studies have shown that progesterone receptor membrane component 1 (Pgrmc1) suppresses fatty liver development and promotes pancreatic insulin secretion 9 , 10 . Although the role of Pgrmc1 has been studied in terms of various metabolic functions, including gluconeogenesis and cholesterol synthesis 11 , 12 , it has not yet been determined whether it is involved in cardiac metabolism. Based on the previous study involving the activation of P450 proteins of PGRMC1 13 , the present study sought to investigate the relationship between Pgrmc1 expression and cardiac pathogenesis including dysfunction of mitochondrial metabolism.…”
Section: Introductionmentioning
confidence: 99%